Identification of Mardivirus Serotypes Circulating in Poultry Farms in Sukabumi and Cianjur District, West Java, 2011 using Multiplex Polymerase Chain Reaction (mPCR) Approach - Risza Hartawan; DharmayantI NLPI (Jurnal Ilmu Ternak dan Veteriner, 2013)
Three serotypes of Mardivirus had been circulating in the farm environments, these being Marek’s disease virus serotype 1 (MDV-1), Gallid hepesvirus 3 (GaHV3) and herpesvirus of turkey (HVT). However, only MDV-1 poses a significant hazard to the poultry farm. The virus causes a neoplastic syndrome that inflicting severe economic loss to the affected farms. Although vaccination has successfully reduced the frequency and severity of outbreaks, the threat does not disappear since several more pathogenic strains have evolved, and these can overcome protection by vaccination. The aim of this study was to investigate the circulation of three Mardivirus serotypes in commercial poultry farms in Sukabumi and Cianjur district using mPCR approach for the feather samples. A low prevalence of these three serotypes was detected. However, the practice of vaccinating using live attenuated MDV-1 caused difficulty in the investigation. Differentation between virulent field strains and CVI988 vaccine strain using the 132 bp repeat motif attenuation marker within the terminal and inverted repeats flanking the unique long region generated an ambiguous result. Thus, other approaches are required to address this issue, such as selection of other markers, restriction fragment length polymorphism (RFLP), high-resolution melt curve analysis (HRM) and gene sequencing. Key Words: Mardivirus serotype, MDV-1, GaHV3, HVT, multiplex PCR